Faktor Risiko Pajanan Pestisida Terhadap Gangguan Kesehatan Petani Bawang Merah Di Kelurahan Kalosi Kecamatan Alla Kabupaten Enrekang - Haerani, Haerani; Ruhban, Andi; Inayah, Inayah; Azizah, Nurul (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
The environment and human health may suffer when pesticides are used frequently and in excessive quantities. This negative impact will cause various health problems such as dizziness, nausea, chest pain and the worst case can cause cancer and even death.The aim of this research was to determine the risk factors for exposure to pesticides on the health problems of shallot farmers in Kalosi Village, Alla District, Enrekang Regency. The type of research used is analytical observational with a cross sectional method. The total number of samples was 97 shallot farmers. Univariate and bivariate data analysis used the chi-square statistical test.The results of the study showed that there was a relationship between pesticide exposure and health problems with length of service with a value of p = 0.007 (p < 0.05), duration of spraying with a value of p = 0.001 (p < 0.05), use of PPE with a value of p = 0.001 (p < 0.05) and spraying frequency with a value of p = 0.089 (p > 0.05) indicating that there is no relationship between pesticide exposure and health problems.The conclusion of this research is that there is a relationship between pesticide exposure to health problems and work period, duration of spraying, use of PPE and there is no relationship between pesticide exposure to health problems and the frequency of spraying among shallot farmers in Kalosi Village, Alla District, Enrekang Regency. It is hoped that farmers will use complete PPE and reduce contact time with pesticides.